2012
DOI: 10.1186/1746-6148-8-113
|View full text |Cite
|
Sign up to set email alerts
|

Presence of an acute phase response in sheep with clinical classical scrapie

Abstract: BackgroundWork with experimental scrapie in sheep has been performed on-site for many years including studies on PrPSc dissemination and histopathology of organs and tissues both at preclinical and clinical stages. In this work serum was sampled at regular intervals from lambs which were infected immediately after birth and from parallel healthy controls, and examined for acute phase proteins. In contrast to earlier experiments, which extensively studied PrPSc dissemination and histopathology in peripheral tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 49 publications
4
19
0
1
Order By: Relevance
“…pSTAT3 and NF-B have been shown to affect transcription at the promoters controlling many of the genes described (i.e., Cxcl10, Ccl4, and A2m) (72)(73)(74)(75)(76), and together they also strongly influence the expression of acute-phase proteins, such as haptoglobin, ceruloplasmin, ␣ 1 -antichymotrypsin, and serum amyloid A (75,77), which are increased in the serum and brain during scrapie infection (unpublished data) (41,78,79). Moreover, components of the NF-B complex, like RelA, can interact directly with STAT3 to alter transcriptional activity (80)(81)(82).…”
Section: Discussionmentioning
confidence: 97%
“…pSTAT3 and NF-B have been shown to affect transcription at the promoters controlling many of the genes described (i.e., Cxcl10, Ccl4, and A2m) (72)(73)(74)(75)(76), and together they also strongly influence the expression of acute-phase proteins, such as haptoglobin, ceruloplasmin, ␣ 1 -antichymotrypsin, and serum amyloid A (75,77), which are increased in the serum and brain during scrapie infection (unpublished data) (41,78,79). Moreover, components of the NF-B complex, like RelA, can interact directly with STAT3 to alter transcriptional activity (80)(81)(82).…”
Section: Discussionmentioning
confidence: 97%
“…Reference values of serum haptoglobin (Hp) and serum amyloid A (SAA) have been determined for pigs, horses, ponies, camels, cows and goats. However, only a few studies have analysed the APPs in sheep (Arslan, Cenesiz, Nisbet, & Yazici, ; Dow, Rogers‐Niemana, Holáskováa, Elsasserb, & Daileya, ; Melling, Bårdsen, & Ulvund, ; Miglio et al, , ; Peetsalu, Tummeleht, Kuks, & Orro, ; Yang et al, ). The APPs have been estimated in neonatal lambs (Peetsalu et al, ), during the pregnancy of ewes, but only in the first six weeks of pregnancy (Dow et al, ), in the period from 60 to 140 days of pregnancy and postpartum, and during the three‐month period of lactation (Miglio et al, ) therefore, they have not been determined strictly in the periparturient period.…”
Section: Introductionmentioning
confidence: 99%
“…As this was the first study in a mouflon herd, no suitable studies were found for relevant comparison. Based on the results obtained from the research of Hp in small ruminants (Kostro et al 2009;Meling et al 2012), we can deliberate that Hp could be the APP that best reflects pathological states; however, in order to obtain more complete and valuable information it is advisable to perform APP profiles including another APP, such as SAA or AGP.…”
Section: Discussionmentioning
confidence: 99%